Methodological approach for the application of the AHP method as a decision tool in mining projects - Silva, Fabiano Della Libera da; Santos, Lucas Backer Lopes Decoté dos; Ricardo, Nadia Ribeiro (Brazilian Journal of Production Engineering, 2025)
Mining is a technological area that still lacks scientific studies and has great potential for advances to be achieved, since it is a sector of the economy that is very important for the country. In recent years, the occurrence of greater price fluctuations in commodities that include mineral products from mining processes has stimulated greater competitiveness in processes, through the application of scientific methods that can support the decisions of managers and technicians in this economic segment. This work uses bibliometrics as a methodological tool, which aims to explore the literature in search of works that use Multicriteria Decision Support Methods, specifically the Analytic Hierarchy Process (AHP), as a decision tool in projects aimed at the mining area. The sequence of steps carried out using the Methodi Ordinatio resulted in ten articles of greater relevance for analysis and systematic reading.
Keywords: Analytic Hierarchy Process (AHP); Decision Support Methods (AMD); Methodi Ordinatio; Mining